Strategies for Implementing Islamic Religious Education in Strengthening Students’ Character at SMA Muhammadiyah 2 Medan - Buchari Muslim (Integrasi: Jurnal Studi Islam dan Humaniora, 2026)
This study aims to analyze the strategies for implementing Islamic Religious Education (IRE) in strengthening students’ character at SMA Muhammadiyah 2 Medan. The research employs a qualitative approach with a case study design. The participants include IRE teachers, the school principal, and students. Data were collected through observation, in-depth interviews, and documentation. The findings reveal that the implementation strategies of IRE are carried out through the integration of Islamic values into classroom learning, habituation of religious activities, teacher role modeling, and the reinforcement of an Islamic school culture. These strategies have proven effective in improving students’ character, including discipline, responsibility, honesty, and religiosity. However, several challenges were identified, such as differences in students’ backgrounds and external environmental influences. Therefore, collaboration among schools, families, and communities is necessary to support the success of character development.